2014
DOI: 10.1179/026708313x13853742547939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior compression on ductility and yielding behaviour in extruded magnesium alloy AZ31

Abstract: In the present paper, the effects of precompression along extrusion direction (ED) on subsequent compression perpendicular to ED were investigated in an extruded magnesium alloy AZ31. The results showed that the yield stress under compression perpendicular to ED increased if there was precompression along ED. The evolution of deformation mechanism was responsible for increase in yield stress because plastic deformation was dominated by both basal slip and {10–12} twinning under compression perpendicular to ED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…After application of a compressive strain of about 0.16, the maximum {0002} pole figure density increases from 9.99 to 14. This evolution of pole figures during compression is consistent with the experimental results of He et al 30,31 and Sarker and Chen. 32 On the basis of the above analysis, there is an obvious difference in texture evolution between…”
Section: Texture Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…After application of a compressive strain of about 0.16, the maximum {0002} pole figure density increases from 9.99 to 14. This evolution of pole figures during compression is consistent with the experimental results of He et al 30,31 and Sarker and Chen. 32 On the basis of the above analysis, there is an obvious difference in texture evolution between…”
Section: Texture Analysissupporting
confidence: 92%
“…This evolution of pole figures during compression is consistent with the experimental results of He et al . 30,31 and Sarker and Chen. 32 On the basis of the above analysis, there is an obvious difference in texture evolution between uniaxial tension and compression, which means that different deformation mechanisms are activated under uniaxial tension and under compression.…”
Section: Texture Analysismentioning
confidence: 99%
“…It can be seen that the basal texture of the as received sheet is divergent and its intensity value is only 7·7, since magnesium alloy usually possess a hcp crystalline structure, the basal slip dominates in the low strain deformation at room temperature. 12,13 Previous studies suggested that it was difficult to activate the compression twin mechanism during tensile deformation at room temperature although the tensile load perpendicular to the c-axis of grains, which attributed to its high CRSS. 14,15 This is the main reason why the twin deformation mechanism did not been activated during the process.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the deformed sheet has large residual stress, which results in poor formability and low stability in mechanical properties. Therefore, the subsequent annealing is required to improve the comprehensive mechanical properties of the deformed sheet [2,3]. Although conventional annealing can reduce residual stress, high-temperature heating not only wastes a lot of time and energy, but also causes grain growth easily and deteriorates mechanical properties [4].…”
Section: Introductionmentioning
confidence: 99%